Ibn Taymiyyah’s Critique of Aristotelian Metaphysics - Zarkasyi, Hamid Fahmy (Afkar: Jurnal Akidah dan Pemikiran Islam, 2010)
Metaphysics has always been one of the pivotal topics of debate between Muslim philosophers; this may especially be said about Ibn Taymiyyah and Ibn Sina. For Ibn Taymiyyah, the subject matter of metaphysics is absolute and universal Existence (al-wujud al-kulli al-mutlaq), namely God, which is known by investigating the intrinsic attributes of His essence (lawahiq al-dhatiyyah). For Ibn Sina, it is al-mawjudat (existing beings), the whole of caused being (kullu mawjud ma‘lul), or the principle abstracted from the whole of caused being, and not God. Such clear and discrete views resulted in different notions of God’s existence as well as of the origination of the universe.